Partisipasi Masyarakat Dalam Perencanaan Pembangunan Tahunan Di Kecamatan Sanana Kabupaten Kepulauan Sula - Usia, Hariyanto; Pribadi, Ulung (Universitas Muhammadiyah Yogyakarta, 2014)
Public participation inside government become universal disclosure that appear concurrent with present him governanceconcept in arrangement government. After become mainstreaming issue governance concept (tata-kelola government)produce various definition. Concept governance refer in institution, process and tradition that determine,how kekuasaaan held, decision made, and voice denizen in hear. Kabupaten local government Sula Isles especiallyKecamatan Sanana to realize government that participative feel shortcoming. Cultivation and government informationgiving to community valued still very minim. To the present time, development planning that participative to needcommunity only claimed unilaterally by government Sula Regency especially Sanana subdistrict has been conductedfor well, and accordance procedure that apply. This research use two approaches outright namely qualitative andquantitative approach. Location research in Sanana subdistrict Sula regency. Data collection conducted with threeway, namely: interview, documentation and questionnaire. Data analysis unit in this research is government SulaRegency, citizen and stakeholder that engage in musrenbang Kecamatan Sanana 2011-2012. Sample withdrawaltechnique in this research is withdrawal sample non random (non probability sampling) namely Purposive Sampling.This result research show community participation level in Musrenbang Sanana subdistrict. In 2011 and 2012 includedin informing category level (level participation where community heard and allowed contend, but they do nothave ability to get guarantee that their view would be considered by holder decision.) That thing in pengaruhi olekfactor internal: age, sex, level of education and work eye points of view. While factor external: government andstakeholder own experience that is more compared by community.